HUB KEBUDAYAAN KOREA SELATAN DI JL. TAMAN KEMANG - Ramdha Rachmansyah; Andi Surya Kurnia (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
As of the global issues in the cultural sector, raises the interest of the community to find out and gather at a point where the culture where can be educated. The global issue regarding cultural trends that had been got from the survey results is the Hallyu Wave, which is the South Korean’s Culture wave that is at the peak of nowadays’s public discussions in the world. The purpose of this study was to determine the communication patterns developed by all levels of society and to determine the process of social integration that is carried out. Site selection and building planning are also need to pay attention to the originals of South Korea's architectural authenticity, which later must be adapted to the Indonesian environment within a surface called hub. This hub is planned with the contextuality of musical analogies method in its architectural implementations, such as the lows-highs and the fronts-backs applications on its architectural, which can rise the integration characteristic of South Korean’s culture in Indonesia, especially in Jl. Taman Kemang, South Jakarta City, where is the one of the many 3rd Place spots in Jakarta Province, and also its adaptations Keywords:  culture; hub; south korea; trend Abstrak Pemanfaatan isu global dalam bidang kebudayaan, memunculkan minat masyarakat untuk mencari tahu dan berkumpul di satu titik dimana kebudayaan yang sedang trend tersebut dapat diedukasikan. Isu global mengenai trend kebudayaan yang didapatkan dari hasil survey adalah Hallyu Wave, yaitu gelombang Kebudayaan Korea Selatan yang sedang berada di puncak pembicaraan masyarakat di dunia. Tujuan penelitian ini untuk mengetahui pola komunikasi yang dibangun oleh seluruh lapisan masyarakat dan untuk mengetahui proses integrasi sosial yang dilakukan. Pemilihan tapak dan pengolahan bangunan juga perlu memperhatikan keaslian arsitektural khas Korea Selatan, yang nantinya harus diadaptasikan pada lingkungan Indonesia yang diwadahkan pada sebuah hub. Hub ini dirancang pada metode perancangan kontekstual musical analogies dalam sisi arsitekturalnya, terutama dalam permainan tinggi-rendah dan maju-mundurnya bidang arsitektural, yang pada akhirnya akan memunculkan karakter integrasi kebudayaan Korea Selatan di Indonesia, khususnya di Jl. Taman Kemang, Kota Administrasi Jakarta Selatan, yang merupakan salah satu pusat 3rd Place untuk Provinsi DKI Jakarta, dan beserta adaptasinya.